Synthesis Characterization and Biological Activities of Coordination Compounds of 4-Hydroxy-3-nitro-2H-chromen-2-one and Its Aminoethanoic Acid and Pyrrolidine-2-carboxylic Acid Mixed Ligand Complexes - Temitayo Aiyelabola; Ezekiel Akinkunmi; Efere Obuotor; Idowu Olawuni; David Isabirye; Johan Jordaan (Bioinorganic Chemistry and Applications)
Coordination compounds of 4-hydroxy-3-nitro-2H-chromen-2-one and their mixed ligand complexes with aminoethanoic acid and pyrrolidine-2-carboxylic acid were synthesized by the reaction of Cu(II) and Zn(II) salts in molar ratio 1 : 2 for the coumarin complexes and 1 : 1 : 1 for the mixed ligand complexes, in basic media. The compounds formed were characterized using infrared, Uv-vis spectrophotometric analyses, mass spectrometry, magnetic susceptibility measurements, and EDX analyses. It was concluded that 4-hydroxy-3-nitro-2H-chromen-2-one coordinated as a monobasic ligand for all the complexes; it also coordinated via the carbonyl moiety in the case of the Cu(II) mixed ligand complexes. Similarly it was proposed that the amino acids also coordinated in a bidentate fashion via their amino nitrogen and carboxylate oxygen atoms. The synthesized compounds were screened for their antimicrobial and cytotoxic activities. The complexes exhibited marginal antimicrobial activity but good cytotoxic activity.